Current regulatory challenges and approaches in the registration of herbal drugs in Europe. (2nd January 2016) - Verma, Nitin
Abstract: Herbal medicines have formed the basis of healthcare worldwide since the earliest times and are still widely used. Recognition of their clinical, pharmaceutical, and economic value is still growing, although this varies widely between countries. Legislative controls in respect of medicinal plants have not evolved around a structured control model. There are different ways in which countries define medicinal plants or herbs or products derived from them, and countries have adopted various approaches to licensing, dispensing, manufacturing, and trading to ensure their safety, quality, and efficacy. The legal situation regarding herbal preparations varies from country to country. A critical problem in the evaluation of herbal drug products is the fact that they are complex mixtures of constituents and the constituents responsible for the therapeutics effects are unknown, which also complicates the stability of these products. A detailed literature survey of the current regulatory challenges and approaches in the registration of herbal drugs in Europe was performed to identify recently introduced changes in regulations or newly introduced regulations compliant with the regulatory bodies.